2021
DOI: 10.7759/cureus.17189
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Pattern and Functional Outcome of Post COVID-19 Syndrome in Older Adults

Abstract: IntroductionCOVID-19 pandemic has been shown to produce high infection rates, significant morbidity and mortality among older adults. A significant proportion of people who have recovered from acute COVID-19 illness seem to suffer from post COVID-19 syndrome. Post COVID-19 syndrome is thought to be a multisystem disease involving physical, functional, mental and psychological domains. This analysis tries to estimate the prevalence, pattern and functional outcomes of post COVID-19 syndrome in hospitalized older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…However, 16 used an unvalidated instrument potentially affecting results. Those finding no significant difference70 79 80 83 84 131 132 135 137 138 153 154 had small sample sizes and only three used a fatigue scale.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, 16 used an unvalidated instrument potentially affecting results. Those finding no significant difference70 79 80 83 84 131 132 135 137 138 153 154 had small sample sizes and only three used a fatigue scale.…”
Section: Resultsmentioning
confidence: 98%
“…One study found the proportion of fatigued participants was higher in the ward group (74%) compared with ICU (33%) 143. Disease severity also had an inconsistent impact on fatigue, with most studies finding no association with severe acute disease or fatigue prevalence in severity categories 80 86 93 130 136 137 153 174–180. Six studies found a significant association with critical illness or a significantly higher proportion of fatigued in severe illness 123 135 145 181–183.…”
Section: Resultsmentioning
confidence: 99%
“…CTRI/2020/11/029264) entitled "prevalence, pattern, and functional outcome of post-COVID-19 syndrome in older adults" done by the same authors for different objectives. The results of the trial were published earlier (24).…”
Section: Methodsmentioning
confidence: 99%
“…3,4 This population also experienced decreased physical function, greater infection-related symptom burden, and reduced quality of life. 5,6 Nurses possess a unique set of skills and insights into providing care to vulnerable populations such as older adults. In particular, pain management nurses-RNs who specialize in pain assessment and management-practice therapeutic communication and counseling, and provide patient and family education across a variety of clinical settings and in the community.…”
mentioning
confidence: 99%